Microwave dielectric properties of CaCu3Ti4O12-Al2O3 composite - Mohd Fariz Ab Rahman; Mohamad Johari Abu; Saniah Ab Karim; Rosyaini Afindi Zaman; Mohd Fadzil Ain; Zainal Arifin Ahmad; Julie Juliewatty Mohamed (2016)
(1-x)CaCu3Ti4O12 + (x)Al2O3 composite (0 ≤ x ≤ 0.25) was prepared via conventional solid-state reaction method. The fabrication of sample was started with synthesizing stoichiometric CCTO from CaCO3, CuO and TiO2 powders, then wet-mixed in deionized water for 24 h. The process was continued with calcined CCTO powder at 900 oC for 12 h before sintered at 1040 oC for 10 h. Next, the calcined CCTO powder with different amount of Al2O3 were mixed for 24 h, then palletized and sintered at 1040 oC for 10. X-ray diffraction analysis on the sintered samples showed that CCTO powder was in a single phase, meanwhile the trace of secondary peaks which belong to CaAl2O4 and Corundum (Al2O3) could be observed in the other samples Scanning electron microscopy analysis showed that the grain size of the sample is firstly increased with addition of Al2O3 (x = 0.01), then become smaller with the x > 0.01. Microwave dielectric properties showed that the addition of Al2O3 (x = 0.01) was remarkably reduced the dielectric loss while slightly increased the dielectric permittivity. However, further addition of Al2O3 was reduced both dielectric loss and permittivity at least for an order of magnitude.